2020
DOI: 10.3389/ffgc.2020.00098
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of the Relationship Between the Effective Cation Exchange Capacity and Soil Organic Carbon Content in Swiss Forest Soils

Abstract: An improved identification of the environmental variables that can be used to predict the content of soil organic carbon (SOC) stored belowground is required to reduce uncertainties in estimating the response of the largest terrestrial carbon reservoir to environmental change. Recent studies indicate that some metal cations can have an active role in the stabilization of SOC, primarily by coordinating the interaction between soil minerals and organic matter through cation bridging and by creating complexes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 55 publications
3
42
0
5
Order By: Relevance
“…Meskipun berstatus sedang, untuk menghindari pencucian hara terutama yang bersifat sangat mobile dan memitigasi potensi erosi, KTK tanah pada lokasi penelitian harus ditingkatkan. Upaya tersebut dapat dilaksanakan melalui ameliorasi bahan organik sebagai penyumbang koloid organik bermuatan variabel /bergantung pH (Solly et al, 2020). Selanjutnya presentase kandungan Kejenuhan basa (KB) tanah lokasi penelitian berstatus sedang.…”
Section: Ktk (Kapasitas Tukar Kation) Dan Kb (Kejenuhan Basa)unclassified
“…Meskipun berstatus sedang, untuk menghindari pencucian hara terutama yang bersifat sangat mobile dan memitigasi potensi erosi, KTK tanah pada lokasi penelitian harus ditingkatkan. Upaya tersebut dapat dilaksanakan melalui ameliorasi bahan organik sebagai penyumbang koloid organik bermuatan variabel /bergantung pH (Solly et al, 2020). Selanjutnya presentase kandungan Kejenuhan basa (KB) tanah lokasi penelitian berstatus sedang.…”
Section: Ktk (Kapasitas Tukar Kation) Dan Kb (Kejenuhan Basa)unclassified
“…Meskipun berstatus sedang hingga tinggi, untuk menghindari pencucian hara terutama yang bersifat sangat mobile dan memitigasi potensi erosi, KTK tanah pada lokasi penelitian harus ditingkatkan. Upaya tersebut dapat dilaksanakan melalui ameliorasi bahan organik (Ngo & Cavagnaro, 2018) sebagai penyumbang koloid organik bermuatan variabel/bergantung pH (Gallez et al, 1976;Solly et al, 2020), mempunyai kompleks jerapan yang sangat luas (Hagemann et al, 2017;Ramos et al, 2018), serta berperan sebagai agregator partikel tanah (Oades 1988;Anda 2008;Possinger et al, 2020). Peneliti lain berupaya meningkatkan KTK tanah melalui penerapan sistem agroforestri (Oorts et al, 2000) dan penanaman tanaman penutup tanah (Nascente et al, 2015).…”
Section: Ktk (Kapasitas Tukar Kation) Dan Kb (Kejenuhan Basa)unclassified
“…The low exchangeable calcium during the major rainy in the subsoil is due to the increased precipitation which resulted in the loss of calcium through leaching and runoff [32]. In their work Solly et al [33] showed that subsoil and topsoil exchangeable calcium is largely a product of organic matter content, pH and presence of other exchangeable cations.…”
Section: Figure 4 Effect Of Gypsum and Seasonal Variability On Soil Solution Calciummentioning
confidence: 99%